2016
DOI: 10.1002/ar.23386
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Potassium Bromate on the Liver of Adult Male Albino Rat and A Possible Protective Role of Vitamin C: Histological, Immunohistochemical, and Biochemical Study

Abstract: Potassium bromate (KBrO 3 ) is a food additive which is used primarily as a maturing agent for flour. It is proved as a toxic agent with significant reduction in the activities of antioxidant capacity. The therapeutic efficacy of vitamin C as antioxidant may provide a possible solution to KBrO 3 mediated oxidative damage. Twenty four adult male albino rats were used to evaluate the protective role of vitamin C against KBrO 3 induced hepatotoxicity and divided into four groups; Group 1 (control), Group 2: recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 37 publications
5
12
0
Order By: Relevance
“…Our result is also supported by Bayomy, Soliman, & Abdelaziz (2016) who found that collagen fibers increased in the portal area of the liver of rats treated with KBrO 3 (20 mg/kg; aqueous) intragastric twice a week for 4 weeks. Authors suggested that this might be due to the damage and dysfunction of mitochondria caused by the reactive oxygen species with lipid peroxidation products leading to cell apoptosis and necrosis and stimulation of a cascade resulting in fibrosis and collagen deposition.…”
Section: Discussionsupporting
confidence: 89%
“…Our result is also supported by Bayomy, Soliman, & Abdelaziz (2016) who found that collagen fibers increased in the portal area of the liver of rats treated with KBrO 3 (20 mg/kg; aqueous) intragastric twice a week for 4 weeks. Authors suggested that this might be due to the damage and dysfunction of mitochondria caused by the reactive oxygen species with lipid peroxidation products leading to cell apoptosis and necrosis and stimulation of a cascade resulting in fibrosis and collagen deposition.…”
Section: Discussionsupporting
confidence: 89%
“…The results also show hepatotoxicity of PB prominently by elevating oxidative stress and affecting the essential macromolecules as well as distortion of structural components of the target cells. The current findings are in accord with the previous work published by Bayomy et al [16].…”
supporting
confidence: 94%
“…They were homed in specially designed commercial plastic animal cages with a controlled condition (22 ± 3°C; 72-77% relative humidity; 12 h day/night cycle) in the Departmental Animal House (Department of Zoology, KSU, Riyadh) on rat pellet diet and fresh tap water ad libitum. The rodents were divided randomly into the five groups: group I (vehicle control treated with saline), group II (potassium bromate at 150 mg/kg body weight as a single dose; [16]), group III (vitamin B 2 at the dose of 2 mg/kg body weight twice a week for a month), group IV (a single dose of potassium bromate at 150 mg/kg body weight followed by vitamin B 2 at the dose of 2 mg/kg body weight twice a week for a month), and group V (a single dose of potassium bromate at 150 mg/kg body weight followed by vitamin B 2 at the dose of 4 mg/kg body weight twice a week for a month). All the test chemicals were administered intraperitoneally in the present work.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, many researchers had been reported the activation of HSC may be closely related to the role of ROS and oxidative stress in stimulating the expression of proinflammatory and profibrotic molecules. [ 46 ]…”
Section: Discussionmentioning
confidence: 99%